Evolution in a plant matrix: adaptive reshaping of kefir grains microbiota and function during long-term soymilk culture - Chen, Zhina; Li, Qingqing; Li, Fanqi; Yin, Linlin; Wang, La; Ye, Tao; Wang, Yi; Fu, Shengju; Wang, Weiming; Huang, Xiaochen (Frontiers in Microbiology, 2025)
To explore the adaptability of kefir grains in long-term subculture in soymilk, this study tracked the succession and functional changes of its microbial community over 4 months. High-throughput sequencing results showed that the microbial community structure was drastically reshaped, mainly manifested in the relative abundance of Lacticaseibacillus kefiranofaciens decreasing from 95.00 to 15.70%, while Lacticaseibacillus paracasei increased from 0.32 to 76.94%, becoming the dominant bacteria. Metagenomic analysis indicated that L. paracasei possesses key enzymes for metabolizing raffinose, stachyose and sucrose, which is the basis for its efficient utilization of soymilk oligosaccharides and its competitive advantage. The decrease in the abundance of L. kefiranofaciens was associated with a decrease in the synthesis of extracellular polysaccharides (EPS), which in turn caused a reduction in the diameter of kefir grains, an increase in surface viscosity and a partial collapse of the gel matrix structure. The pH and free amino acid content of fermented soymilk did not fluctuate much during the passage process, but the sensory acceptance, antioxidant capacity and angiotensin converting enzyme (ACE) inhibitory activity all showed a downward trend. This work reveals the adaptive evolution mechanism of kefir grains in a plant matrix environment and provides a theoretical basis for the optimization of soymilk fermentation based on limited strains.